SSusceptibility of Dermestes Maculatus Degeer (Coleoptera: Dermestidea) Larvae Infesting Smoked African Catfish (Clarias Gariepinus) to Alchornea Cordifolia (Schum. & Thonn.) Leaf Powder - Dr. Charles Kwesi Koomson Koomson; Collins Owusu-Fordjour; Ambrose Darku (Hasanuddin University, 2022)
The efficacy of the plant powder of Alchornea cordifolia was evaluated under laboratory conditions against the larvae of the leather beetle Dermestes maculatus which is a major fish pest that cause serious damage when left uncontrolled. The experiment was in concentrations of 0g, 1.0g, 2.0g, 2.5g, 3.0g admixed with 15g of smoked fish powder; while all the treatment containing 0g were without plant powder which served as control, all the treatment were in triplicates. Newly emerged (0 - 72 hours old) larvae of D. maculatus were introduced. Evaluation of the potency of the plant powder was based on larvae mortality and the adult emergence. The weight losses in fish muscle in the treated and untreated samples were compared as index of fish damage during storage. The result showed that higher plant powder concentration were significantly (P<0.05) effective in killing larvae stage of the insect as well as the larvae at 1st and 2nd weeks after infestation (WAI). Adult emergence was significantly (P<0.05) inhibited in the treated fish and weight loss due to insect infestation was greatly suppressed by the higher dosage rate of the plant powder compared to control. The findings showed that efficiency of A. cordifolia leaf powder is dosage dependent and is capable of controlling the larval stage of D. maculatus in smoked fish (Clarias gariepinus) during storage. It is therefore recommended that plant could be used by poor resource fish farmers, processors and marketers in protecting smoked-dried fish against D. maculatus during processing, transportation, marketing and storage.